Impact of COVID-19 on mental health and quality of life among undergraduate nursing students and nurse internes - Dawood, Eman; Mitsu, Rufa; Ghadeer, Hend Al; Abusaleh, Razan; Harbie, Farah Al; Alenazi, Ashawag; Alwahibee, Lujain (Palembang MediRose Publisher, 2023)
Background: COVID-19 pandemic had seriously impacted various aspects of all societies globally. The pandemic has the potential to affect all people including college students, with a large number of students experiencing psychological distress which became a growing universal concern. Objective: The aim of this study was to examine the impact of COVID-19 on mental health and quality of life among undergraduate nursing students and nurse internes. Methods: A cross-sectional research design was used, and data was collected from 264 participants using a demographic data sheet, the Patient Health Questionnaire-4, and the WHOQOL-BREF Scale. Data were analyzed using JMP Pro 15. Results: The sample consisted mostly of nursing students (88.64%) from various academic levels, including 30% nurse interns. Among them, 34.85% had a history of COVID-19 symptoms, and 43.18% tested positive for COVID-19. Overall, participants reported high satisfaction with their quality of life, receiving necessary information for daily life, having improved relationships and support from friends and family compared to normal times, and having good access to healthcare services. Additionally, their faith and spiritual practices showed improvement. Regarding mental health, there was a significant correlation between perceived mental health and previous COVID-19 symptoms, while social support showed a significant correlation with quality of life. Conclusions: Those nursing students and nurse interns who experienced negative psychological health impacts due to COVID-19 need to be referred for proper mental health counseling and other treatment services.